2015
DOI: 10.1088/0004-637x/806/2/151
|View full text |Cite
|
Sign up to set email alerts
|

STABILITY OF EXTRATERRESTRIAL GLYCINE UNDER ENERGETIC PARTICLE RADIATION ESTIMATED FROM 2 keV ELECTRON BOMBARDMENT EXPERIMENTS

Abstract: The destruction of solid glycine under irradiation with 2 keV electrons has been investigated by means of IR spectroscopy. Destruction cross sections, radiolysis yields, and half-life doses were determined for samples at 20, 40, 90, and 300 K. The thickness of the irradiated samples was kept below the estimated penetration depth of the electrons. No significant differences were obtained in the experiments below 90 K, but the destruction cross section at 300 K was larger by a factor of 2. The radiolysis yields … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 48 publications
2
16
0
Order By: Relevance
“…Alterations in the IR spectra of the pure glycine samples can be induced when irradiated with high-energy electrons during the experiments. This can be verified when comparing the irradiated sample spectra (Figure 1(D)) to the pristine sample (Figure 1(E)) measured at 10 K: keeping the sample at this temperature for 1 hr does not alter its IR spectrum at all, whereas irradiating the sample for the same time causes significant changes in it, which is in complete agreement with the results of previous experimental works (Pilling et al 2014;Maté et al 2014Maté et al , 2015. In general, all features decrease and broaden upon irradiation; the simultaneous degradation, amorphization, and oligomerization (to oligopeptides, (-HN-CH 2 -CO-) n ; Kaiser et al 2013;Pilling et al 2013) of the crystalline organic sample may account for this phenomenon.…”
Section: Infrared Spectrum Of Glycinesupporting
confidence: 90%
See 1 more Smart Citation
“…Alterations in the IR spectra of the pure glycine samples can be induced when irradiated with high-energy electrons during the experiments. This can be verified when comparing the irradiated sample spectra (Figure 1(D)) to the pristine sample (Figure 1(E)) measured at 10 K: keeping the sample at this temperature for 1 hr does not alter its IR spectrum at all, whereas irradiating the sample for the same time causes significant changes in it, which is in complete agreement with the results of previous experimental works (Pilling et al 2014;Maté et al 2014Maté et al , 2015. In general, all features decrease and broaden upon irradiation; the simultaneous degradation, amorphization, and oligomerization (to oligopeptides, (-HN-CH 2 -CO-) n ; Kaiser et al 2013;Pilling et al 2013) of the crystalline organic sample may account for this phenomenon.…”
Section: Infrared Spectrum Of Glycinesupporting
confidence: 90%
“…The few hundred nanometer thick layer of amino acid could not be destroyed; the 60 nm H 2 O ice layer deposited on top of the amino acids provided a partial shielding from the energetic electrons. Another recent paper investigated the stability of a thin glycine film (90 nm) toward exposure to 2 keV electrons (Maté et al 2015). Destruction cross sections, which are proportional to the rate of destruction, radiolysis yields, and half-lifes for samples were reported for 20, 40, 90, and 300 K. Interestingly, the authors concluded that the rate of destruction is invariant of the temperature; further, the decay rate of β-glycine was found to be larger by a factor of two at 300 K compared to the low temperatures, at which the zwitterionic amorphous form prevails.…”
Section: Introductionmentioning
confidence: 99%
“…Pilling et al irradiated glycine with 1 MeV H + in order to study the stability of different polymorph configurations [17]. Pilling et al [18], Maté et al [19], and Souza-Corrêa et al [20] studied its dissociation by keV electrons. UV radiolysis was performed by Peeters et al [21] and by Ferreira-Rodrigues et al [22].…”
Section: Introductionmentioning
confidence: 99%
“…Glycine, the simplest amino acid, has been detected in solar system objects and its presence is suspected, though not yet firmly established, 2 in the interstellar medium (ISM) where molecules of comparable complexity have been observed. [4][5][6][7][8] and references therein. 1 Once formed, glycine would tend to remain on the grains in cold environments, but would desorb from the grains with rising temperature.…”
Section: Introductionmentioning
confidence: 99%